Respuesta :

Answer:

∠BEC = 54°

Step-by-step explanation:

ED and EA are opposite rays, which means that they form a straight angle.

Straight angle = 180°

Which means that,

∠AEB + ∠BEC +∠DEC = ∠AED

This is the equation we are going to use,

We also know that ∠CED = 72°

We know that BE bisects ∠AEC

Know, we know that ∠AEB =  (7x - 2)°

That means ∠BEC = (7x - 2)°  - This is because ∠AEB = ∠BEC

=>(7x - 2)° + (7x - 2)° + 72° = 180°

=> (14x - 4)° + 72° = 180°

=> (14x - 4)° = 180° - 72°

=> (14x - 4)° = 108°

=> 14x = 108° + 4°

=> 14x = 112°

=> x = (112 / 14)°

=> x = 8°

So, know we can find ∠BEC

(7x - 2)°

=> (7 * 8 - 2)°

=> (56 - 2)°

=> 54°

If my answer helped, kindly mark me as the Brainliest!!

Thank You!!

ACCESS MORE